2016
DOI: 10.1021/acs.jpcc.6b07444
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Analysis on CH4–CO2 Swapping Phenomenon Occurred in Hydrates

Abstract: Swapping CH 4 with CO 2 in hydrocarbon hydrates is renowned as an eco-friendly method for potential energy production and climate change mitigation. To fully understand the CH 4 −CO 2 replacement process, in situ Raman spectroscopy combined with long-term macroscopic measurements were carried out by putting CH 4 hydrates into gaseous CO 2 at temperatures ranging from 273.2 to 281.2 K. A kinetic model based on gas diffusion theory was modified. Results showed that the gas swapping process started with surface r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2018
2018
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 40 publications
1
23
0
2
Order By: Relevance
“…4, which represent the kinetic characteristics of hydrate decomposition in the six particle size deposits and bulk hydrate, respectively. We can clearly observe the Raman peak of the water molecules in the main structure of the hydrate caused by vibration of the H-O bond and distributed in the Raman shi range of 2830-3600 cm À1 , which is also observed by Zhou et al 45 and Schicks et al 46 Compared with the bulk hydrate decomposition process, it was found that the behavior of the hydrate formed in sediment was signicantly different. As shown in Fig.…”
Section: Analysis Of Raman Resultssupporting
confidence: 72%
“…4, which represent the kinetic characteristics of hydrate decomposition in the six particle size deposits and bulk hydrate, respectively. We can clearly observe the Raman peak of the water molecules in the main structure of the hydrate caused by vibration of the H-O bond and distributed in the Raman shi range of 2830-3600 cm À1 , which is also observed by Zhou et al 45 and Schicks et al 46 Compared with the bulk hydrate decomposition process, it was found that the behavior of the hydrate formed in sediment was signicantly different. As shown in Fig.…”
Section: Analysis Of Raman Resultssupporting
confidence: 72%
“…43 Many studies, including field campaigns, continue to be conducted to determine the optimal operation conditions (T, P, addition of liquid vs. gaseous CO2) to enhance CH4 removal from hydrates. [44][45][46][47][48][49][50] Because it is a very aggressive hydrate former, H2S is proposed as an additive for this application, 48,51 and it could help improving the kinetics of the CO2/CH4 swap process.…”
Section: Selected Promising Technological Applications Of Gas Hydratesmentioning
confidence: 99%
“…Detailed information concerning the two devices can be found elsewhere. 30 The SEM images were obtained using Hitachi S-4800 equipped with a cryo-SEM preparation system (Quorum). The measurement time was limited to 40 minutes to avoid the potential dissociation of the formed hydrate.…”
Section: Apparatusmentioning
confidence: 99%
“…As seen, the surface of the hydrate sample is porous and the pore size is generally below 5 mm, which agrees with literature. 30 However, the morphology of the samples formed from the 0.18 wt% LPB solution is greatly changed. No pores are found on the surface.…”
Section: Microscopic Measurementsmentioning
confidence: 99%